Implementasi Nilai Pendidikan Fikih untuk Membentuk Karakter Santri - Fatriyah, Danang Uswatun; Khotimah, Khusnul (JoEMS (Journal of Education and Management Studies), 2023)
This research was undertaken with the objective of examining the procedures involved in incorporating Islamic religious principles into fiqh education at the Abdul Hadi Islamic Boarding School in Jombang, with the aim of nurturing and developing the character of the students. The study utilized a descriptive qualitative approach, employing observation and interview methods to gather relevant data. The findings of the research indicate that the Abdul Hadi Islamic Boarding School has effectively implemented the teachings of Islamic jurisprudence, with a notable favorable impact on the intellectual and moral development of the students at Abdul Hadi Jombang.